Biodiversity of Soil Fungi on Integrated Pest Management Farming System - Anton Muhibuddin; Luaili Addina; Abdul Latief Abadi; Athoillah Ahmad (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
The greatest problem of modern agricultural practices is the use of chemical pesticides and fertilizers. It is noted that about 40% of the world's land surface is used for agriculture. The way this agricultural land is managed has a great influence on the global environment. Integrated Pest Management (IPM) farming system produces fewer negative externally affects, can effectively restore ecosystems and deliver well ecosystem services. Depending on methods applied and degree of production, agricultural practices impact biodiversity in the ecosystem and it also influences conservation practices within the ecosystem. The result showed that diversity of soil fungi on IPM was higher than diversity on conventional one. Trichoderma sp. and Acremonium sp. which are known as antagonist fungi were found on IPM but not on conventional one. Domination Index on IPM was lower than conventional field. Bacterial leaf blight (Xanthomonas oryzae) disease intensity showed no difference on both systems. The yield on IPM was higher (6.34 ton/ha) than conventional field (5.56 ton/ha). It has been found that rich biodiversity in agricultural environment improves productivity of agricultural systems. The IPM system gives more regard to the soil fungi biodiversity and considers it as an integrated system upon which the success of the agricultural production depends.Keywords : Integrated Pest Management, biodiversity, soil fungi, modern agricultural